2022
DOI: 10.14324/111.444/000119.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reflections, Resilience, and Recovery: A qualitative study of COVID-19's impact on an international adult population’s mental health and priorities for support

Abstract: The impact of the coronavirus 2019 (COVID-19) pandemic on different countries and populations is well documented in quantitative studies, with some studies showing stable mental health symptoms and others showing fluctuating symptoms. However, the reasons behind why some symptoms are stable and others change are under-explored, which in turn makes identifying the types of support needed by participants themselves challenging. To address these gaps, this study thematically analysed 925 qualitative responses fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It is no surprise that lockdown restrictions – a legally imposed physical detachment from others aimed to keep everyone safe in order to decrease coronavirus transmission in the community – have taken a toll on everyone. In Wong et al [ 13 ], the authors present a rich qualitative summary of the variety of impacts that study respondents have experienced when reflecting on the pandemic 12 months after. Crucially, the authors also identified the variety of support that respondents would need in order to recover.…”
mentioning
confidence: 99%
“…It is no surprise that lockdown restrictions – a legally imposed physical detachment from others aimed to keep everyone safe in order to decrease coronavirus transmission in the community – have taken a toll on everyone. In Wong et al [ 13 ], the authors present a rich qualitative summary of the variety of impacts that study respondents have experienced when reflecting on the pandemic 12 months after. Crucially, the authors also identified the variety of support that respondents would need in order to recover.…”
mentioning
confidence: 99%